Sex Differences in Mitral Annular Calcification and the Clinical Implications - Seo, Jiwon; Jeong, Hyeonju; Cho, Iksung; Hong, Geu-Ru; Ha, Jong-Won; Shim, Chi Young (Frontiers in Cardiovascular Medicine, 2021)
Background: Heterogeneous mechanisms may contribute to the occurrence of mitral annular calcification (MAC), however, little is known about the sex differences in MAC and the clinical implications of these differences. This study aimed to investigate clinical and imaging differences of MAC according to sex. Methods: In total, 537 patients (221 men) with MAC were identified by transthoracic echocardiography at a single center from January 2012 to June 2016. Moderate-to-severe MAC was defined as calcification extent ≥120 degrees of the mitral annulus. Significant functional mitral stenosis (MS) was defined as a transmitral mean diastolic pressure gradient ≥5 mmHg. Results: Women more frequently had moderate-to-severe MAC and concomitant mitral regurgitation than men; however, significant functional MS was comparable between sexes. In the logistic regression analysis, old age, uncontrolled hypertension, end-stage renal disease (ESRD), and obstructive hypertrophic cardiomyopathy were significantly associated with moderate-to-severe MAC in women, whereas ESRD and moderate-to-severe aortic stenosis were in men. In the Cox regression analysis, significant functional MS was associated with all-cause death in both sexes, although an independent association was found in only women. Conclusion: Women had more extended MAC than men. Significant functional MS was independently associated with unfavorable clinical outcomes in patients with MAC, which was more pronounced in women than in men.